Cheops : Salon Curieux : Keramiek. - De Beyerd, Breda (Breda : De Beyerd, 1988)
Brandt, Rob ; Dijkstra, Tjitske ; Hooft, Marja ; Kuipers, Michel ; van Leeuwen, Jan
Cheops : Salon Curieux : Keramiek/Ceramics, De Beyerd, Breda, 11.9.88 t/m 23.10.88
boek